Spatial frequency heterodyne imaging of aqueous phase transitions inside multi-walled carbon nanotubes. Issue 46 (9th November 2015) - Schunk, F. M.; Rand, D.; Rose-Petruck, C.
Abstract : Spatial frequency heterodyne imaging of aqueous phase transitions in carbon nanotubes demonstrates the applicability of thermodynamics to nano-confined water. Abstract : The evaporation and condensation of water on multi-walled carbon nanotube (MWCNT) surfaces was studied as a function of temperature and time using X-ray spatial frequency heterodyne imaging (SFHI). SFHI is an imaging modality that produces an absorption and scatter image in a single exposure, and has increased sensitivity to variations in electron density relative to more common place X-ray imaging techniques. Differing features exhibited in the temporal scatter intensity profiles recorded during evaporation and condensation revealed the existence of an absorption–desorption hysteresis. Effects on the aforementioned phenomena due to chemical functionalization of the carbon nanotube surfaces were also monitored. The increased interaction potential between the functionalized MWCNT walls and water molecules altered the evaporation event time scale and increased the temperature at which condensation could take place. Theoretical calculations were used to correlate the shape of the observed scatter profiles during condensation to changes in the MWCNT cross section geometry and configuration of the contained water volume. Changes in evaporation time scales with temperature coincided with the boiling point for confined water predicted by the Kelvin equation, indicating that a thermodynamic description of mesoscopic confined water is permissible in some instances.